Investigation of anti-diabetic effect of a novel coenzyme Q10 derivative - Tan, Xiaojun; Yang, Xinyi; Xu, Xun; Peng, Yuwei; Li, Xin; Deng, Yongxing; Zhang, Xueyang; Qiu, Wenlong; Wu, Dudu; Ruan, Yongdui; Zhi, Chen (Frontiers in Chemistry, 2023)
Introduction: The rising incidence of type 2 diabetes has seriously affected international public health. The search for more drugs that can effectively treat diabetes has become a cutting-edge trend in research. Coenzyme Q10 (CoQ10) has attracted much attention in the last decade due to its wide range of biological activities. Many researchers have explored the clinical effects of CoQ10 in patients with type 2 diabetes. However, CoQ10 has low bio-availability due to its high lipophilicity. Therefore, we have structurally optimized CoQ10 in an attempt to exploit the potential of its pharmacological activity. Methods: A novel coenzyme Q10 derivative (L-50) was designed and synthesized by introducing a group containing bromine atom and hydroxyl at the terminal of coenzyme Q10 (CoQ10), and the antidiabetic effect of L-50 was investigated by cellular assays and animal experiments. Results: Cytotoxicity results showed that L-50 was comparatively low toxicity to HepG2 cells. Hypoglycemic assays indicated that L-50 could increase glucose uptake in IR-HepG2 cells, with significantly enhanced hypoglycemic capacity compared to the CoQ10. In addition, L-50 improved cellular utilization of glucose through reduction of reactive oxygen species (ROS) accumulated in insulin-resistant HepG2 cells (IR-HepG2) and regulation of JNK/AKT/GSK3β signaling pathway, resulting in hypoglycemic effects. Furthermore, the animal experiments demonstrated that L-50 could restore the body weight of HFD/STZ mice. Notably, the findings suggested that L-50 could improve glycemic and lipid metabolism in HFD/STZ mice. Moreover, L-50 could increase fasting insulin levels (FINS) in HFD/STZ mice, leading to a decrease in fasting blood glucose (FBG) and hepatic glycogen. Furthermore, L-50 could recover triglycerides (TG), total cholesterol (T-CHO), lipoprotein (LDL-C) and high-density lipoprotein (HDL-C) levels in HFD/STZ mice. Discussion: The addition of a bromine atom and a hydroxyl group to CoQ10 could enhance its anti-diabetic activity. It is anticipated that L-50 could be a promising new agent for T2DM.